HONOUR OF THE SOLDIER - Golta, Iveta (Administrative and Criminal Justice, 2021)
In the Republic of Latvia, a soldier performs public service in the field of national defence and his/her legal status is a right guaranteed by the state, statutory duties, restrictions, and disciplinary liability, which are currently regulated by military law, administrative law and administrative procedure law. In addition to the regulation of special and general legal norms, a soldier also has important and binding moral values, because in Latvia "honour" is a characteristic of a soldier, which is inextricably linked to the soldier's profession both historically and of military service. Within the framework of the paper, the author has studied the concepts, essence, genesis and development of such values of a soldier as "honour" and "dignity", from the historical and modern point of view, both in civil life and military science. The author has also clarified their role in the legal status of a soldier and concluded that the existing legal status of a soldier should be elaborated and can be defined as a right guaranteed nowadays. Although not explicitly defined, it should be included in the legal status of a soldier as a military ethical requirement for his dignity and trust, integrity and duty in the performance by the state, statutory duties and restrictions, disciplinary liability and honor as a military ethical requirement.